Aerodynamic conductances in a sparse mixed oak woodland (Quercus rotundifolia Lam. and Quercus suber L.) - Pereira, F.L. (2011)
The study of heat and mass exchange between the vegetation and its local environment plays a central role in the analysis of plant-atmosphere interactions. These studies can be undertaken at different scales, ranging from individual leaves to isolated trees or even the canopy scale. In each of these cases, heat and mass fluxes depend on the use of adequate values of transfer conductances. Within a broader study on interception loss from a sparse cork and holm oak woodland (montado) of Southern Portugal, aerodynamic conductances were determined for the boundary layers of both leaves (LBL) and the entire canopy.